Cognitive predictors of skilled performance with an advanced upper limb multifunction prosthesis: a preliminary analysis. (4th July 2017) - Hancock, Laura; Correia, Stephen; Ahern, David; Barredo, Jennifer; Resnik, Linda
Abstract: Purpose The objectives were to 1) identify major cognitive domains involved in learning to use the DEKA Arm; 2) specify cognitive domain-specific skills associated with basic versus advanced users; and 3) examine whether baseline memory and executive function predicted learning.Method Sample included 35 persons with upper limb amputation. Subjects were administered a brief neuropsychological test battery prior to start of DEKA Arm training, as well as physical performance measures at the onset of, and following training. Multiple regression models controlling for age and including neuropsychological tests were developed to predict physical performance scores. Prosthetic performance scores were divided into quartiles and independent samples t-tests compared neuropsychological test scores of advanced scorers and basic scorers. Baseline neuropsychological test scores were used to predict change in scores on physical performance measures across time.Results Cognitive domains of attention and processing speed were statistically significantly related to proficiency of DEKA Arm use and predicted level of proficiency.Conclusions Results support use of neuropsychological tests to predict learning and use of a multifunctional prosthesis. Assessment of cognitive status at the outset of training may help set expectations for the duration and outcomes of treatment. Implications for Rehabilitation: Cognitive domains of attention and processing speed were significantly related to level of proficiencyof an advanced multifunctional prosthesis (the DEKA Arm) after training. Results provide initial support for the use of neuropsychological tests to predict advanced learningand use of a multifunctional prosthesis in upper-limb amputees. Results suggest that assessment of patients' cognitive status at the outset of upper limb prosthetictraining may, in the future, help patients, their families and therapists set expectations for theduration and intensity of training and may help set reasonable proficiency goals.